Burden in family caregivers of the elderly: prevalence and association with characteristics of the elderly and the caregivers - Lara de Sa Neves Loureiro; Maria das Gracas Melo Fernandes; Sueli Marques; Maria Miriam Lima da Nobrega; Rosalina A. Partezani Rodrigues (SciELO, 2013)
A cross-sectional, epidemiological study aimed to estimate the prevalence of burden among family caregivers of impaired elderly residents in the city of João Pessoa, and to identify associations between the mean burden and social and demographic characteristics of the elderly and the caregivers. A total number of 240 elderly residents in a previously drawn census tract participated in this research. The sample was composed of 52 elderly and their caregivers. For data collection, a questionnaire was applied with questions on social and demographic characteristics of elderly and caregivers, and the Burden Interview Scale was used. Results showed a high prevalence of burden among caregivers (84.6%), in which a statistically significant association was found with the following characteristics: retired elderly, elderly as head of family, spousal caregivers, and caregivers with less education. The findings of this study may contribute to the development of activities focused on formal and emotional support for the caregivers.